2021
DOI: 10.1051/shsconf/202111001022
|View full text |Cite
|
Sign up to set email alerts
|

Features of Heavy Metal Contamination of Agricultural Soils in the Kursk Region of Russia and Economic Assessment of Restoration

Abstract: Kursk region of Russia has unique fertile soils. Heavy metals are among the factors that pollute the soil. The article is devoted to the study of the spatial distribution of heavy metals in soils. The relevance of the study is that the value of the soil is determined by its value for obtaining environmentally friendly agricultural products. Data on the content of heavy metals in the soil can prevent intensive cultivation of crops. The task of the work is to identify heavy metals that predominate in the soils o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This could explain why many HM are found to be greater than some reference values and other study in site Wk 4 . Tomakov and Tomakov, (2021) reported that Pb has a cumulative effect and causes damage to the central and peripheral nervous system; human health is in danger through food chain. Excessive pollution of site Wk 4 could affect the marine ecosystem of the downstream Lake.…”
Section: Eri and Permentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain why many HM are found to be greater than some reference values and other study in site Wk 4 . Tomakov and Tomakov, (2021) reported that Pb has a cumulative effect and causes damage to the central and peripheral nervous system; human health is in danger through food chain. Excessive pollution of site Wk 4 could affect the marine ecosystem of the downstream Lake.…”
Section: Eri and Permentioning
confidence: 99%
“…For the case study Mo concentrations are very high. Knowing that Mo belongs to the second class of danger and has a General toxic, carcinogenic and mutagenic effect at significant concentrations (Tomakov and Tomakov, 2021); it can be dangerous for human and environment. In addition, a diet rich in molybdenum caused deformities in the joints of the extremities of cattle; so, this high concentration in molybdenum exposed also animals present in the agroecosystem.…”
Section: Eri and Permentioning
confidence: 99%
See 1 more Smart Citation
“…Охрана труда является важной обязанностью работодателя по обеспечению государственных нормативных требований охраны труда и одним из важнейших приоритетов деятельности любых организаций всех форм собственности. Однако на предприятиях различных сфер экономики Курской области производственный травматизм продолжает оставаться одной из актуальных социально-экономических проблем, поскольку имеют место несчастные случаи со смертельным исходом [1,2]. При многоотраслевом укладе экономики региона наиболее высокий уровень производственного травматизма со смертельным исходом регистрируется в строительстве [3,4].…”
unclassified
“…Подавляющее большинство причин производственного травматизма на предприятиях региона случается по вине руководителей и самих работников -они не в полной мере выполняют возложенные на них функции и обязанности [1,2].…”
unclassified